Quantifying Genetic Diversity Based on Morphological and Molecular Analysis in Pearl millet [Pennisetum glaucum (L.) R. Br.] Inbred Lines - Renu Rani; Vikas Khandelwal; Sunita Jhunjhadia; Supriya Ambawat; Sushila Bhanwariya; Amninder Singh; Vinay Kumar (Annals of Arid Zone, 2024)
The experiment was carried out with thirty pearl millet inbred lines at Research Farm of ICAR-AICRP on Pearl Millet, Project Coordinating Unit, Mandor-Jodhpur during kharif 2020 in randomized block design (RBD) with three replications. Morphological and molecular diversity was assessed in 30 pearl millet inbred lines by Mahalanobis D2 analysis and Simple Sequence Repeats (SSR) molecular marker, respectively. Total five clusters were formed from D2 analysis and seven clusters were generated from SSR markers data analysis. The character viz. panicle girth, number of effective tillers per plant and 1000 seed weight contributed maximum to morphological diversity. The clustering pattern based on SSR markers data revealed that genotypes at molecular level had high diversity as compared to that seen at phenotypic level. There was significant differences among the clustering pattern of D2 and SSR molecular marker analysis. The reason may be environmental influence on phenotypic level. This information can be used as selection criteria to have hybridization between diverse parents to exploit heterosis in pearl millet breeding program.